Analisis Karakteristik Disturbansi Frekuensi 9 – 150 Khz Pada Sistem Photovoltaic Terhadap Tipe Beban Induktif - Muhammad, Nagib; Utami, Budi; Setiana, Hatib (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
The Solar Power Plant converts light into electricity using photovoltaic. It uses an inverter to convert DC to AC electricity to be connected to an AC load. Along with the increasing use of solar panel, inverter use has also increased. In fact, the inverter can produce disturbances at frequency between 9-150kHz. Based on this matter, this study is focused on observing the disturbance characteristics of photovoltaic system due to variations in irradiation and inductive load in the frequency range from 9 - 150 kHz. It is expected that the output of this observations can be a reference for research in analyzing, predicting and knowing the effects on the electric power system. First, this observation provide inductive type of load then observe it in at least two different solar irradiation conditions. Based on observations obtained, in general there are three frequencies of dominant disturbances, namely the range 19-29kHz, 69-79Khz, and 140-149kHz.